STRUCTURAL SYNTHESIS OF A SIX-LINK PERCUSSION MECHANISM WITH THE LARGEST CONNECTING ROD (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
In this paper, the synthesis of a six-link impact mechanism with the largest connecting rod with improved kinematic and dynamic parameters based on a crank-rocker and twocrank hinged-four-link mechanisms with special positions of the links is considered.
Keywords: Special position, link, connecting rod, mechanism, synthesis